ANALISIS KUALITAS PELAYANAN PEMBUATAN IJIN MENDIRIKAN BANGUNAN DI BADAN PELAYANAN PERIJINAN TERPADU KOTA SEMARANG - Agnes Galih Chris Roseita; Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The research took the title of Quality Analysis Services Manufacturing Building Permit (IMB) in the Integrated Licensing Service Agency of Semarang. During this time in the minds of the public, Building Permit Service ( IMB ) sounds a bit complicated and convoluted, long service process and less than optimal. Therefore, the problem in this research is how the service quality manufacture of building permits , What are the contributing factors in the manufacture of building permits and what should be done to optimize the service manufacture of building permits ( IMB ) in the Integrated Licensing Service Agency ( BPPT ) of Semarang. The focus of this research is the quality of Building Permit licensing services. The purpose of this research is to determine the quality of service the manufacture of building permits in the Integrated Licensing Services Agency of Semarang. This research used a qualitative research with descriptive approach. The techniques of data collection is by interview , observation and documentation , in the form of documents and records that have relation with service quality in the Building Permit Integrated Licensing Service Agency ( BPPT ) of Semarang. The results showed that the Integrated Licensing Service Agency (BPPT ) of Semarang in providing Building Permit Service ( IMB ) is already well although there are still some deficiencies, such as infrastructure and human resources . The conclusion of this research is that Building Permit Service ( IMB ) service in the Integrated Licensing Services Agency ( BPPT ) of Semarang is already well although there are still some things that have not been optimal and needs to be repaired. The researchers suggest that the services from Integrated Licensing Services Agency ( BPPT ) of Semarang should be more professional, effective, efficient, and correct the deficiencies to make it more optimal.